2016
DOI: 10.1155/2016/2721719
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the N-Terminal C2 Domain fromArabidopsis thalianaPhospholipase Dαand Dβ

Abstract: Most of plant phospholipases D (PLD) exhibit a C2-lipid binding domain of around 130 amino acid residues at their N-terminal region, involved in their Ca2+-dependent membrane binding. In this study, we expressed and partially purified catalytically active PLDα from Arabidopsis thaliana (AtPLDα) in the yeast Pichia pastoris. The N-terminal amino acid sequence of the recombinant AtPLDα was found to be NVEETIGV and thus to lack the first 35 amino acid belonging to the C2 domain, as found in other recombinant or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…These results indicate that also the (His) 6 tag has a great influence on the interfacial binding preference of VpPLD to different phospholipid monolayers. The effect of the (His) 6 tag on the binding and hydrolytic activity of PLD was demonstrated in other studies [24,25,26]. The previous studies and the present results strongly indicate that the effect of the His tag should be taken into consideration when comparing the binding properties or the activities of proteins.…”
Section: Resultssupporting
confidence: 81%
“…These results indicate that also the (His) 6 tag has a great influence on the interfacial binding preference of VpPLD to different phospholipid monolayers. The effect of the (His) 6 tag on the binding and hydrolytic activity of PLD was demonstrated in other studies [24,25,26]. The previous studies and the present results strongly indicate that the effect of the His tag should be taken into consideration when comparing the binding properties or the activities of proteins.…”
Section: Resultssupporting
confidence: 81%
“…One predicted PLD in Chloroidium sp. UTEX 3007 contains several C2 calcium-binding domains, indicating that it acts on membrane phospholipids to produce membrane-bound phosphatidic acid (PA) and cytosolic choline ( Rahier et al, 2016 ). PA has noted roles in environmental stress response ( Peppino Margutti et al, 2017 ), and its liberation has been shown to create ‘supersized’ lipid droplets ( Fei et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Qu et al (2014) discovered that the up-regulated expression of the PLD gene in Vicia faba root tips and Arabidopsis thaliana could induce stomatal closure and H 2 O 2 production (Qu et al 2014). More importantly, Phospholipase D (PLD, EC 3.1.4.4) is a type of lipolytic enzyme that hydrolyzes lecithin, phosphatidylethanolamine, and phosphatidylglycerol under the induction of Ca 2+ , and αPLD also hydrolyzed phosphatidylinositol diphosphate under acidic or Ca 2+ stimulation (Rahier et al 2016). Previous studies have found that calcium signaling deeply involved in the formation of R. glutinosa replanting disease (Yang et al 2015).…”
Section: Discussionmentioning
confidence: 99%